A Hubungan Agama dan Negara dalam Perspektif Sejarah Hukum - Atma Hajri, Wira; nufus, hayatun; Bur , Arifin; diansyah, Ar (UIR Law Review, 2024)
Abstract : The relationship between religion and the state in Indonesia is always interesting to discuss even though the First Principle of Pancasila explicitly mentions "Belief in One Almighty God", even this is included again in Article 29 paragraph (1) of the 1945 Constitution. Formulation of the First Principle and Article 29 Paragraph (1) of the 1945 Constitution is of course the starting point for discussing the relationship between religion and the state. This research is different from previous studies related to the relationship between religion and the state. The point of difference is the aim of this research which focuses on the benefits obtained from the issue of the relationship between religion and the state from a legal historical perspective. The research results show that there is a close relationship between religion and the state in Indonesia even though it does not directly mention a particular religion in the 1945 Constitution or other statutory regulations. This relationship can be seen in several quotes from Soekarno's speech on 1 June 1945, the history of the birth of the principle of belief in one and only God, and the presidential decree on 5 July 1959. So, the view that Indonesia is a religiously neutral country is ahistorical. Keywords: Religion, State, Legal History